Retrospective study on assessment of risk for gestational diabetes using fetal medicine foundation’s gestational diabetes risk assessment calculator in a tertiary care hospital in coastal Karnataka, India - Ganiga, Pradeep; Subhash, Vivek V. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: Gestational diabetes is defined as impaired glucose tolerance with onset or first recognition during pregnancy. Undiagnosed or inadequately treated gestational diabetes can lead to significant maternal and fetal complications. Even though there are guidelines for diagnosis of GDM (gestational diabetes mellitus) by the Government of India, there is poor penetration of the implementation throughout the nation. Methods: The study was conducted in A. J. Institute of Medical Sciences between April to June 2019. 56 patients were evaluated with the fetal medicine foundation GDM risk calculator to assess the risk for gestational diabetes in a retrospective approach. Results: Incidence of GDM in the study was 15.9%. At a cut-off of 1/80, the calculator predicted increased risk for 37 out of 56 patients. There was a sensitivity of 91.6% and specificity of 63.6% with a negative predictive value of 96.5% and positive predictive value of 29.5%. there was a false positive rate of 43.2%. Conclusions: The fetal medicine foundation GDM risk calculator will prove to be an invaluable tool to predict high risk patients who need closer monitoring of blood glucose into the third trimester.